Functional Shift in the Old Church Slavonic Hymnography: the Liturgical Service for Serbia’s Saint Illuminators and Teachers (August 30) in the Srbljak of 1861 and 1986 - Темчин, Сергей Юрьевич Юрьевич (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]The author demonstrates that the Serbian liturgical service for Serbia’s Saint Illuminators and Teachers (to be sung on August 30) which was most probably compiled in the late 18th-mid-19th century consists almost exclusively of hymns extracted from the earlier Old Church Slavonic hymnographic compositions, both translated from Greek and the original (composed in Moscovite Rus). For the majority of troparia as well as for some stichera, their hymnographic sources and the principles of their editing while including them into the Serbian composition are indicated. Among the researched hymns (the majority of stichera are not included in the research), there are merely three troparia which may be considered original. The resulted hymnographic composition is a clear example of the functional shift in the Old Church Slavonic hymnography, but also a remarkable piece of evidence for the Russian-Serbian cultural contacts in the field of liturgical literature of the late 18th-mid-19th century.
Keywords: Old Church Slavonic hymnography, Srbljak, Russian-Serbian cultural relations